Cambridge reading adventures: a tale of two sinbads: 3 explorers - Shahab Shamshirsaz (UK Cambridge University Press, 2017)
The Tale of Sinbad the Sailor narrates the legendary sea voyages of a wealthy merchant, Sinbad of Baghdad, who recounts seven perilous and extraordinary journeys across distant seas. Each voyage unveils exotic lands, monstrous creatures, and supernatural events. Though Sinbad is often driven by curiosity or commercial ambition, he consistently faces shipwrecks, treacherous landscapes, and mythical beings like the giant roc and the Old Man of the Sea. In every tale, Sinbad survives through a mix of wit, resilience, and fortune. Despite immense hardships, he amasses riches and wisdom, returning to Baghdad after each adventure. The stories are framed by Sinbad the Sailor narrating his experiences to Sinbad the Porter, a poor man, emphasizing the contrasts of fate and the value of perseverance and gratitude. The collection explores themes of destiny, divine justice, human ingenuity, and the pursuit of knowledge through travel and trial.